Halal Food Supply Chain Implementation Model: A Measurement Development and Validation / Wan Marhaini Wan Omar and Shams Rahman - Wan Omar, Wan Marhaini; Rahman, Shams (Human Resource Management Academic Research Society, 2018)
The global demand for halal food products is growing throughout the world. However, research in halal food supply chain is relatively new. This study is conducted to develop and validate a measurement instrument for the halal food supply chain (HFSC) implementation model and confirms it as a higher-order construct. The measurement items of the dimensions used in the model are developed and validated based on a comprehensive multi-step approach prior to the large-scale survey. A questionnaire-based survey is distributed to 600 Malaysian halal certified food and beverage organisations. A total of 240 usable questionnaires are collected to confirm the underlying dimensions empirically. Confirmatory factor analysis is conducted to define the model of HFSC implementation and to confirm the HFSC implementation as a higher-order construct. The results revealed that nine dimensions are crucial and significantly define HFSC implementation as a higher- order construct. To our knowledge this is the first attempt to develop and validate the measurement instrument for HFSC implementation model. Theoretically this study contributes to the body of knowledge in defining and confirming the HFSC implementation as a higher-order construct. Furthermore, it provides a valid measurement instrument for further halal research in the context of other countries and markets.